A Multidimensional Poverty Index for Latin America - Santos, M; Villatoro, P (Wiley, 2016)
This paper proposes a new Multidimensional Poverty Index for Latin America. The index combines monetary and non-monetary indicators, updates deprivation cut-offs for certain traditional unsatisfied basic needs indicators and includes some new indicators, aiming to maximize regional comparability within the data constraints. The index is estimated for 17 countries of the region in two points in time – one around 2005 and the other around 2012. Overall, we estimate about 28% of people are multidimensionally poor in 2012 in the region. We find statistically significant reductions of poverty in most countries, both in terms of incidence and intensity over the period under analysis. However, important disparities between rural and urban areas remain. Statistical scrutiny of the index suggests that it captures the state of poverty relatively well while maintaining a certain parsimony and being highly robust to changes in weights, indicators, and poverty cut-off.